Photosynthesis in Ranunculus asiaticus L.: The Influence of the Hybrid and the Preparation Procedure of Tuberous Roots - Carillo, Petronia; Arena, Carmen; Modarelli, Giuseppe Carlo; De Pascale, Stefania; Paradiso, Roberta (Frontiers in Plant Science, 2019)
Ranunculus asiaticus L. is a quantitative long-day geophyte grown in cold greenhouse for cut flowers and potted plants. Flowering in ranunculus is a complex process, strongly steered by temperature and photoperiod. Vernalization of rehydrated tuberous roots anticipates sprouting and leaf rosette formation and flowering. It is known that the time for flowering and the sensitivity to cold treatment in term of flowering anticipation vary in the numerous hybrids, while no information seems to be available on the influence of the hybrid and of vernalization on photosynthetic process and primary metabolites profiling. We investigated the influence of two hybrids, MDR and MBO, and two preparation procedures of tuberous roots, only rehydration (Control, C) and rehydration followed by vernalization (V), on photosynthesis and photochemistry of plants of R. asiaticus grown in climatic chamber, under controlled environment. In addition, in MBO plants, in which vernalization showed the main effects, carbohydrate, amino acid and protein levels were also investigated. In control plants, the response of leaf photosynthesis to increasing white light revealed higher photosynthetic activity in MDR than in MBO. Quantum yield of PSII (PSII), electron transport rate (ETR) and non-photochemical quenching (NPQ) did not differ between the hybrids. The maximal photochemical efficiency (Fv/Fm) was higher in MBO than in MDR and showed a decrease in both hybrids after vernalization. The preparation treatment of propagation material affected differently the light response of photosynthesis in the two hybrids, which increased in plants from vernalized tuberous roots compared to those from only rehydrated in MBO and decreased in MDR, in accordance to the effects of vernalization observed in leaf photosynthetic pigments. In MBO vernalized tuberous roots, starch was rapidly degraded and the carbon skeletons used to synthesize amino acids. Control plants of MBO developed more leaves than those of MDR and a consequent higher plant leaf area. Compared to only rehydration, vernalization of rehydrated tuberous roots increased the plant leaf area in both the hybrids. Compared to control, vernalized tuberous roots of MBO showed higher concentrations of sucrose and free amino acids, which could act as a long-distance signal promoting floral transition in young leaf primordia.